Kenya : political activities : : Kikuyu Central Association - Great Britain; National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 1929)
Government memoranda and reports relating to the Kikuyu Central Association, land rights and other topics including female circumcision